Quality of life (QoL) for people with primary sclerosing cholangitis (PSC): a pragmatic strategy for identifying relevant QoL issues for rare disease - Elena Marcus; Patrick Stone; Douglas Thorburn; Martine Walmsley; Bella Vivat (SpringerOpen, 2022)
Abstract Background Primary sclerosing cholangitis (PSC) is a rare incurable disease of the bile ducts and liver which can significantly impair quality of life (QoL). No existing QoL tools are entirely suitable for people living with PSC (PwPSC). We aimed to develop a measure of QoL for PwPSC in the UK, beginning by identifying relevant QoL issues. This paper describes our approach to this first stage, and discusses related benefits and limitations. Methods Scientific consensus on how to reliably stage PSC is lacking, due to its rarity and heterogeneity. We initially hypothesised four categories for PSC severity. After beginning the study, these were revised to six. For such a rare disease, the study could not recruit sufficient participants in each of these categories, particularly the more severe, in the time available. We therefore modified the design, adapting standard methodology for identifying potentially relevant issues. We started by conducting a thematic analysis of data from a previous survey of PwPSC, and extracting QoL issues from a literature review of QoL questionnaires of relevance to PwPSC. We then conducted group and individual interviews with PwPSC and clinicians, investigating the relevance, importance, phrasing, and breadth of coverage of issues identified. We also explored the validity of our hypothesised categories for disease severity. Results We identified 1,052 potentially relevant QoL issues from the survey and literature review and took 396 of these forwards for discussion with 28 PwPSC. We found 168/396 issues were considered relevant by ≥ 60% of these participants. We then discussed this subset of 168 issues with 11 clinicians. PSC and clinician participants identified some problematic phrasing with 19 issues, due to potential upset (n = 12) or problems with understanding (n = 7). We included one new issue from those suggested. Conclusion We identified a range of QoL issues relevant to PwPSC, with a good breadth of coverage, although lacking an in-depth understanding of the PSC experience. Our strategy effectively identified relevant QoL issues for people living with this rare condition, for which there is no consensus on stratifying for its severity. This strategy should however be considered specific to such circumstances, not a general recommendation for an alternative approach.